Pengaruh Abu Tempurung Kelapa Sebagai Substitusi Sebagian Semen terhadap Kuat Tekan Beton K-250 - M. Fajar Rhamadhani; Rasio Hepiyanto; Prima Eko Agustyawan (Universitas Batanghari Jambi, 2026)
Concrete is one of the most widely used construction materials. Therefore, efforts are needed to reduce cement consumption by utilizing waste materials, one of which is coconut shell ash. This study aimed to determine the effect of partially replacing cement with coconut shell ash on the compressive strength of K-250 concrete. An experimental method was employed using coconut shell ash replacement levels of 0%, 2%, 4%, and 6% by the weight of cement, with compressive strength testing conducted at 28 days. The average compressive strength of normal concrete was 20.81 MPa, while concrete with 2%, 4%, and 6% coconut shell ash substitution achieved average compressive strengths of 19.25 MPa, 18.35 MPa, and 17.85 MPa, respectively. The results indicate that increasing the percentage of coconut shell ash substitution tends to reduce the compressive strength of concrete. Therefore, the use of coconut shell ash as a partial replacement for cement at the substitution levels investigated was not able to improve the compressive strength of K-250 concrete.